Respuesta :

EXPLANATION:

Given;

We are given the exponential equation shown below;

[tex](\frac{125}{8})^{4x-1}=(\frac{4^2}{25^2})^{x+1}[/tex]

Required;

We are required to

(i) Find a common base

(ii) Solve for x

Step by step solution;

To solve this problem we shall start with the following steps;

[tex][(\frac{5}{2})^3]^{4x-1}=[(\frac{2}{5})^4]^{x+1}[/tex]

For the left side of the equation, we can refine by applying the rule of exponents;

[tex]\begin{gathered} Flip\text{ the left side of the equation:} \\ (\frac{2}{5})^{-3} \end{gathered}[/tex]

Therefore, we now have;

[tex][(\frac{2}{5})^{-3}]^{4x-1}=[(\frac{2}{5})^4]^{x+1}[/tex][tex](\frac{2}{5})^{-12x+3}=(\frac{2}{5})^{4x+4}[/tex]

We now have a common base and that means;

[tex]\begin{gathered} If: \\ a^x=a^y \\ Then: \\ x=y \end{gathered}[/tex]

Therefore;

[tex]-12x+3=4x+4[/tex][tex]-12x-4x=4-3[/tex][tex]-16x=1[/tex]

Divide both sides by -16;

[tex]x=-\frac{1}{16}[/tex]

ANSWER:

[tex]x=-\frac{1}{16}[/tex]

ACCESS MORE